2023
DOI: 10.2196/48166
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Digital Health Literacy Interventions in Older Adults: Single-Arm Meta-Analysis

Abstract: Background In a world of rapid digital technology development, the lack of digital health literacy (DHL) among older people cannot be ignored. DHL is becoming an essential competency that can facilitate the health status and health management of older adults. DHL interventions that are feasible and appropriate can be implemented on a large scale through the health care system for older people. Objective The purpose of this meta-analysis was to assess th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…With the digitization of health care and the wide availability of Web-based applications, DHL is an essential skill to be mastered in the digital age, which is an important determinant of health ( 12 ) and has a profound impact on an individual’s health ( 13 ). Existing research has shown that DHL could alleviate anxiety related to both physical health and the usage of digital technology among older adults ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…With the digitization of health care and the wide availability of Web-based applications, DHL is an essential skill to be mastered in the digital age, which is an important determinant of health ( 12 ) and has a profound impact on an individual’s health ( 13 ). Existing research has shown that DHL could alleviate anxiety related to both physical health and the usage of digital technology among older adults ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly implemented measures are scales about digital health literacy (DHL) or affinity to technology [ 46 ], which reflects competence and knowledge but does not directly relate to motivation. Some populations have low DHL [ 47 ], but increasing DHL is possible [ 48 ]. Higher DHL may increase the benefits of DHIs, as shown for health literacy [ 49 ].…”
Section: Discussionmentioning
confidence: 99%